2008
DOI: 10.1007/s00122-008-0920-2
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and validation of quantitative trait loci for resistance to Cercospora zeae-maydis infection in tropical maize (Zea mays L.)

Abstract: Breeding for resistance to gray leaf spot, caused by Cercospora zeae-maydis (Cz) is paramount for many maize environments, in particular under warm and humid growing conditions. In this study, we mapped and characterized quantitative trait loci (QTL) involved in the resistance of maize against Cz. We confirmed the impact of the QTL on disease severity using near-isogenic lines (NILs), and estimated their effects on three major agronomic traits using their respective near isogenic hybrids (NIHs), which we obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 29 publications
5
41
1
4
Order By: Relevance
“…In some of these reports, additive gene effects were linked with QTL regions mapped on chromosome 2 by Bubeck et al (1993), on chromosome 1 by Saghai-Maroof et al (1996) and also on chromosome 4 by Gordon et al (2004). Our results are consistent with most of the reports in the literature, in that previous studies revealed that additive effects account for more than 90% of the variability among generations and that GLS resistant could be: i) inherited additively, ii) controlled by additive gene action and presenting minor dominant and epistatic contributions, iii) associated with the general combining ability of inbred lines, and iv) controlled by few effective factors (Clement et al, 2000;Julliati et al, 2009;Pozar et al, 2009). The results and inferences about GLS genetic resistance obtained in this study would be different from previously reported studies if least square estimates were applied, since a high influence of epistasis was observed on scaling-test (data not shown).…”
Section: Bayesian Genetic Controlsupporting
confidence: 88%
“…In some of these reports, additive gene effects were linked with QTL regions mapped on chromosome 2 by Bubeck et al (1993), on chromosome 1 by Saghai-Maroof et al (1996) and also on chromosome 4 by Gordon et al (2004). Our results are consistent with most of the reports in the literature, in that previous studies revealed that additive effects account for more than 90% of the variability among generations and that GLS resistant could be: i) inherited additively, ii) controlled by additive gene action and presenting minor dominant and epistatic contributions, iii) associated with the general combining ability of inbred lines, and iv) controlled by few effective factors (Clement et al, 2000;Julliati et al, 2009;Pozar et al, 2009). The results and inferences about GLS genetic resistance obtained in this study would be different from previously reported studies if least square estimates were applied, since a high influence of epistasis was observed on scaling-test (data not shown).…”
Section: Bayesian Genetic Controlsupporting
confidence: 88%
“…In research conducted by Pozar et al (2009) in Brazil, QTLs related to gray leaf spot resistance have been mapped and characterized through SNP and SSR markers.…”
Section: Methodsmentioning
confidence: 99%
“…This species is cultivated in many different environments and climates at different latitudes, from Russia to Argentina. The culture has a wide geographic range of cultivation and can be developed in many different soil and climate conditions; consequently, it is possible to use various commercial hybrids that have sundry tolerance levels to leaf and grain pathogens (Pozar, Butruille, Diniz, & Viglioni, 2009). The occurrence of these pathogens causes reductions in grain yield and grain health quality because infection by these fungi results in paralysis of the normal process of grain filling and reduces maize cob weight.…”
Section: Introductionmentioning
confidence: 99%
“…However, the development of cultivars with genetic resistance to disease is costly and laborious, since it involves numerous selection cycles and favorable environmental conditions for the pathogen's development, as well as for the expression of resistance in segregating populations. Thus, QTL mapping (Quantitative Trait Loci) to disease resistance using molecular markers may accelerate the development of resistant genotypes, maximizing the yield potential of crops by means of marker-assisted selection (Pozar et al 2009). The literature indicates that a few genes with additive and dominant gene action control resistance to ALB (Badu-Apraku et al 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Studies aiming to know the nature and magnitude of the effects of resistance genes are important to guide the breeding procedures in order to introduce new resistance alleles in susceptible germplasm, and maximize the use of genetic variability in populations under selection (Pozar et al 2009). Thus, determining the number, the nature of gene action, and the position of QTL in the maize consensus map can significantly contribute to the clarification of the genetic basis of resistance to ALB in tropical maize germplasm.…”
Section: Introductionmentioning
confidence: 99%